Parents' Effective Time Endowment and Divorce: Evidence from Extended School Days - María Padilla-Romo; Cecilia Peluffo; Mariana Viollaz (Institute of Labor Economics (IZA), 2022)
Policies that extend the school day in elementary school provide an implicit childcare subsidy for families. As such, they can affect parents' time allocation and family dynamics. This paper examines how extending the school day affects families by focusing on marriage dissolution. We exploit the staggered adoption of a policy that extended the availability of full-time elementary schools across different municipalities in Mexico. Using administrative data on divorces, we find that the extension in the school day by 3.5 hours leads to a significant increase in divorce rates. Moreover, the effect grows with every year of municipalities' exposure to full-time schooling. Increased female employment due to the availability of childcare is likely to be one of the mechanisms that relaxed restrictions to marriage dissolution.
Keywords: J12; J13; J18; 330; divorce; childcare; full-time schools